Análise fitoquímica e alelopatia de leguminosas arbóreas sobre a germinação e o desenvolvimento do milho - Mendonça, Lorena Camargo de (2015)
Agroforestry systems, such as alley cropping, combine the cultivation of forest plants with agricultural crops, being a viable alternative for management and soil conservation, since they promote the of fertilizer usage by recycling nutrientres present in the trees leaves . In such systems, it is important to know which tree species will be used and the effects that its secondary metabolites can promote on agricultural species. This effect, called allelopathy, is caused by the presence of allelochemicals, which may harm or benefit from the development of another species or organism. Therefore, the objective of this study was to evaluate the allelopathic effect of two legume trees Parapiptadenia rigida (Benth.) Brenan. and Schizolobium parahyba (Vell.) on the germination and development of corn. The experiments performed in the laboratory were the identification tests of secondary compounds and corn germination . For the phytochemicals tests, the dried crushed material was submitted to exhaustive and successive extraction with chloroform and ethanol. Following tests were performed in the presence and absence of secondary compounds and their extracts were used for testing corn seeds germination. The species dried leaves were also used for the preparation of the extracts at concentrations of 0; 1; 2.5; 5; 7.5 to 10%, for the tests of corn germination and growth . The experiment in greenhouse was carried out in two steps that were evaluated at 55 and 120 days, respectively. Maize seedlings were added in pots in which were applied treatments of S. parahyba powder, P. rigida powder and the control (without addition of powder). Corn development was analyzed by measuring height, diameter and number of leaves, chlorophyll content, dry weight of shoot and root and analysis of minerals in the leaves. The phytochemicals tests found the allelochemicals tannins, catechins, steroids and triterpenoids, flavonoids, saponins and alkaloids for P. rigida and tannins, steroids and triterpenoids, flavonoids and alkaloids for S. parahyba. In the germination bioassay of P. rigida, the extract with chloroform and ethanol S. parahyba delayed corn germination compared to the control, which may have been due to the extraction of allelochemicals The results indicate that the S. parahyba extract promoted delay in the corn germination when compared to the P. rigida extract. However, none of the species damaged the germination percentage. In the seedling development test, the S. parahyba extract increased average length of shoot, while reduced the average length of root with greater effect in relation to P. rigida. In the test greenhouse test, there was no statistical difference between treatments, compared to the control, for two evaluation stages. Therefore, neither legume species showed any negative allelopathic effect for the corn, when tested in a greenhouse and can be considered good alternatives for cultivating with corn in an alley cropping system.